1997
DOI: 10.1128/cdli.4.2.156-167.1997
|View full text |Cite
|
Sign up to set email alerts
|

Standardization and a multilaboratory comparison of Neisseria meningitidis serogroup A and C serum bactericidal assays. The Multilaboratory Study Group

Abstract: A standardized serum bactericidal assay (SBA) is required to evaluate the functional activity of antibody produced in response to Neisseria meningitidis serogroup A and C vaccines. We evaluated assay parameters (assay buffer, target strains, growth of target cells, target cell number, complement source and concentration, and methods for growth of surviving bacteria) which may affect the reproducibility of SBA titers. The various assay parameters and specificity of anticapsular antibody to five serogroup A stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
150
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 400 publications
(152 citation statements)
references
References 37 publications
2
150
0
Order By: Relevance
“…Although the early SBA advocated the use of human complement [17], in more recent years, with the need for standardisation and also the unavailability of large volumes of suitable human complement, baby rabbit serum was suggested as an alternative complement source [16,28,29]. Recently, studies for both serogroups A and C, including the present one, have highlighted that meningococci are more sensitive to baby rabbit complement than human complement resulting in higher titres.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the early SBA advocated the use of human complement [17], in more recent years, with the need for standardisation and also the unavailability of large volumes of suitable human complement, baby rabbit serum was suggested as an alternative complement source [16,28,29]. Recently, studies for both serogroups A and C, including the present one, have highlighted that meningococci are more sensitive to baby rabbit complement than human complement resulting in higher titres.…”
Section: Discussionmentioning
confidence: 99%
“…The calibration factor of the standard CDC 1992 serum for serogroup C-speci¢c IgG used in both Oac 3 and Oac assays was 24.1 Wg ml 31 for the standard assay and 19.6 EU ml 31 for the assay to detect primarily high avidity antibody. SBAs were performed as described by Maslanka et al [16] with either baby rabbit sera (Pel-Freeze Incorporated, Rodgerson, AZ, USA) or human sera as an exogenous complement source. The target strain used throughout was C11 (C :16:P1.1,7 a ).…”
Section: Serological Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Probably, other mechanisms besides the bactericidal response can also provide protective immunity against serogroup B meningococci. For serogroups A and C a standardized assay was designed using rabbit serum as a complement source, since this is readily available [25]. However, the use of infant rabbit complement results in much higher SBA titers than the use of human complement and a recent paper showed that this assay lacks sensitivity in predicting a protective titer as assessed by Goldschneider et al [1,2] using human complement [26].…”
Section: Sbamentioning
confidence: 99%
“…Serum bactericidal antibodies (SBA) were determined according to standardised methodology [28] using a complement source of 25% baby rabbit complement (Pelfreeze) and N. meningitidis serogroup C strain C11 as the target strain. Titres are expressed as the reciprocal of the ¢nal dilution producing v 50% bactericidal killing after 60 min [29].…”
Section: Serum Bactericidal Assaymentioning
confidence: 99%